Tumefactive Multiple Sclerosis in Taiwan - Kuan, Yi-Chun (Public Library of Science, 2013)
BACKGROUND: Multiple sclerosis (MS) is less common in Asia, including Taiwan, and some characteristics of MS in Asians differ from those of Caucasians. Tumefactive brain lesion is even rarer in MS patients. OBJECTIVE: To review patients with tumefactive MS and compare them with those in other studies investigating tumefactive demyelinating lesions and our Taiwanese typical MS patients. METHODS: Twelve patients (6.3%) from the 190 MS patients visiting Taipei Veterans General Hospital from 1985 to 2010 were enrolled. They all fulfilled the McDonald or Poser criteria for MS and had at least one brain lesion larger than 2 centimeters with or without a mass effect. RESULTS: Eleven patients (91.7%) were female and presented tumefactive brain lesions during the first attack. The clinical course of all patients was relapsing-remitting with a second attack within 2 years. Their initial extended disability status score was higher, but the prognosis was better after more than 2 years of follow-up, than in other studies. Moreover, our patients did not have optic or spinal involvement as well as positive neuromyelitis optica immunoglobulin or aquaporin-4 antibody, which is very common in Taiwanese MS patients. CONCLUSION: Tumefactive MS is not common in Taiwan. Although the tumefactive demyelinating lesions seem to be terrible initially, their prognosis is relatively more favorable than expected.